Hervormers wat ons nie mag vergeet nie - Van der Merwe, J. M. (Verbum et ecclesia, 1997)
Church Reformers we should not forget. On thefifth of November 1980, the Reformed Day Witness was published in Die Kerkbode by eight theologians of the Dutch Reformed Church. The Witness, as it became known, soon had storm clouds gathering in the church, because of it's content. It was a wakeup call to the church about it's prophetic call, it's guidance to government and it's role in reconciliation. Many ministers and members of the church supported The Witness while church leadership was mainly against it. In the end The Witness was silenced but the seed were sown. Many ministers and church members now knew that the Dutch Reformed Church had to take a new approach with regard to it's prophetic call and it's role in society. When we look back over what happened in the past seventeen years, history tells us that these men were prophets of their time, men that we must not forget.